Evaluation of Gingival crevicular Fluid Levels of Myeloperoxidase after non-surgical periodontal therapy of Smoker patients having chronic periodontitis - Doha Basuony Abdel Aziz Ghobashy (2012)
include arabic summary .
referances (72-97) .
Ms d in oral medicine
Cario University , Faculty of Oral and Dental medicine .
Keywords: chronic periodontitis